Insights into the role of RD3 in guanylate cyclase trafficking, photoreceptor degeneration, and Leber congenital amaurosis - Molday, Laurie L.; Jefferies, Thomas; Molday, Robert S. (Frontiers in Molecular Neuroscience, 2014)
RD3 is an evolutionarily conserved 23 kDa protein expressed in rod and cone photoreceptor cells. Mutations in the gene encoding RD3 resulting in unstable non-functional C-terminal truncated proteins are responsible for early onset photoreceptor degeneration in Leber Congenital Amaurosis 12 (LCA12) patients, the rd3 mice, and the rcd2 collies. Recent studies have shown that RD3 interacts with guanylate cyclases GC1 and GC2 in retinal cell extracts and HEK293 cells co-expressing GC and RD3. This interaction inhibits GC catalytic activity and promotes the exit of GC1 and GC2 from the endoplasmic reticulum and their trafficking to photoreceptor outer segments. Adeno-associated viral vector delivery of the normal RD3 gene to photoreceptors of the Rd3 mouse restores GC1 and GC2 expression and outer segment localization and leads to the long-term recovery of visual function and photoreceptor cell survival. This review focuses on the genetic and biochemical studies that have provided insight into the role of RD3 in photoreceptor function and survival.